Sheltered in Safe Hands - A Study on the Usage and Effectiveness of ‘Kavalan’ SOS App among Women in Tamil Nadu (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As we progress towards digital era, using smart phones to ensure safety of citizens, especially women is seen as a great relief. After the gory crime of Delhi gang rape in 2012, the government has introduced various safety measures to protect women, one of which is the development of safety apps. Though there are many safety apps for women, this study focuses on ‘Kavalan’ app, which was launched in 2018 by Tamil Nadu police to ensure women safety. This mobile application seems to have a wide reach as soon it was launched and efforts have been taken by the police department to make sure that citizens are aware of the mobile app. The present study focuses on few questions like the reach of the app in rural areas, and women who do not know to use technology and tries to find the answer through survey and in-depth interviews.